Pelatihan Dasar Pemasaran Digital Sebagai Upaya Memperluas Jaringan Pemasaran Produk Pertanian Kelompok Tani Desa Sidomulyo Kabupaten Mojokerto Provinsi Jawa Timur - Rijanto, Achmad; Rahayuningsih, Suesthi; Ardiantoro, Luki (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
Seno hamlet, Sidomulyo village, Mojokerto regency, East Java province. The problem faced by the partners was the lack of knowledge and skills regarding digital marketing for agricultural products. So far, marketing of the partners' agricultural products has mostly been done through word of mouth, resulting in a limited marketing reach primarily around Sidomulyo village in Mojokerto regency. This has led to slow sales growth for the partners' agricultural products. The solution implemented was to provide knowledge and skills to the partners about the fundamentals of digital marketing for agricultural products. The aim of this community service activity was to enhance the knowledge and skills of the partners regarding the basics of digital marketing, enabling them to market their agricultural products more widely through digital media. The method used involves providing knowledge and skills to the partners about the fundamentals of digital marketing for agricultural products in the form of training, as well as evaluating the level of knowledge and skills of the training participants. This method was carried out through lectures, discussions, and practical sessions. The results of this community service activity show that 10% of the training participants have excellent knowledge and skills in the fundamentals of digital marketing for agricultural products, 70% have good criteria, and 30% have fairly good criteria. From this community service activity, it can be concluded that this effort increases the number of farmer group members who have knowledge and skills regarding digital marketing for agricultural products.